Power and Cultures of the World. Developing New Social Architectures of Influence in the UN: A Network Analysis. - García-Faroldi, Livia; Bello, Valeria (Hipatia Press, 2021)
The most important sociologists have discussed whether it is the social structure that produces individual behaviours or the latters are only the results of individuals’ will. In the literature of international relations, as well, a similar debate about the structure-agency problem has developed: in this context, the central question is whether or not there exist external sources of influences for the decisions that states take in international politics. This article, by sharing an integrative and post-structural approach (Archer, 1995; Foucault, 1970) proposes an empirical analysis of the formation of power architectures within the UN-SC surrounding the question of Intercultural Dialogue. A Social Network Analysis checks whether the way actors exercise power is concurrently the result of individual wills whose contents follows both institutional and cultural conditioning. Findings show that there is not a fixed structure of power relations which can be given for granted but it is continuously negotiated through both practices and social interactions. However, both institutional and, above all, cultural factors shape power relations.
Keywords: Estructura social; Redes sociales; Intercultural dialogue; Power; Social network analysis; International relations; Culture